Does journal endorsement of reporting guidelines influence the completeness of reporting of health research? A systematic review protocol. - Shamseer, L; Stevens, A; Skidmore, B; Turner, L; Altman, D; Hirst, A; Hoey, J; Palepu, A; Simera, I; Schulz, K; Moher, D (2012)
BACKGROUND: Reporting of health research is often inadequate and incomplete. Complete and transparent reporting is imperative to enable readers to assess the validity of research findings for use in healthcare and policy decision-making. To this end, many guidelines, aimed at improving the quality of health research reports, have been developed for reporting a variety of research types. Despite efforts, many reporting guidelines are underused. In order to increase their uptake, evidence of their effectiveness is important and will provide authors, peer reviewers and editors with an important resource for use and implementation of pertinent guidance. The objective of this study was to assess whether endorsement of reporting guidelines by journals influences the completeness of reporting of health studies. METHODS: Guidelines providing a minimum set of items to guide authors in reporting a specific type of research, developed with explicit methodology, and using a consensus process will be identified from an earlier systematic review and from the EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Network's reporting guidelines library. MEDLINE, EMBASE, the Cochrane Methodology Register and Scopus will be searched for evaluations of those reporting guidelines; relevant evaluations from the recently conducted CONSORT systematic review will also be included. Single data extraction with 10% verification of study characteristics, 20% of outcomes and complete verification of aspects of study validity will be carried out. We will include evaluations of reporting guidelines that assess the completeness of reporting: (1) before and after journal endorsement, and/or (2) between endorsing and non-endorsing journals. For a given guideline, analyses will be conducted for individual and the total sum of items. When possible, standard, pooled effects with 99% confidence intervals using random effects models will be calculated. DISCUSSION: Evidence on which guidelines have been evaluated and which are associated with improved completeness of reporting is important for various stakeholders, including editors who consider which guidelines to endorse in their journal editorial policies.